Reliability and Validity of Patient-Reported, Rater-Based, and Hybrid Physical Activity Assessments in COPD: A Systematic Review. (1st November 2020) - Gore, Shweta; Chindam, Tirupathi; Goldberg, Allon; Huang, Min H.; Shoemaker, Michael; Blackwood, Jennifer
Abstract: Selecting valid and reliable PA assessments in chronic obstructive pulmonary disease (COPD) is crucial to ensure that the information obtained is accurate, valuable, and meaningful. The purpose of this systematic review was to compare the validity and reliability among PA assessments in COPD. An electronic database search of PubMed and CINAHL was completed in December 2019 using MeSH terms on physical activity, COPD, validation, and questionnaires. Transparency in reporting was assessed with the STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) checklist while methodological quality was assessed with the modified Quality Appraisal tool for Reliability studies (QAREL) for reliability studies and the Quality Appraisal of Validity Studies (QAVALS) for validity studies. The search yielded fifteen different measures. The Stanford 7-day recall (PAR) demonstrated the strongest correlations with SenseWear Armband on energy expenditure ( r = 0.83; p < 0.001) and moderate correlations for time spent in activity over 3 METs ( r = 0.54, p < 0.001). The Multimedia Activity Recall (MARCA) also demonstrated moderate to good correlations with both SenseWear and Actigraph GT3X + accelerometers ( r = 0.66–0.74). Assisted and computerized PRO measures (PAR and MARCA) and hybrid measures (C-PPAC and D-PPAC) demonstrate better psychometric properties as compared to other subjective measures and may be considered for quantification of PA in COPD. However, observations drawn from single validation studies limit strength of recommendations and further research is needed to replicate the findings.